A CRITIQUE OF THE REVISED STATEMENT OF ACCOUNTING PRINCIPLES. - Husband, George R. (The Accounting Review, 1942)
The revised statement of "Accounting Principles," prepared by the Executive Committee of the American Accounting Association and published in the June 1941 issue of "The Accounting Review," is a decided improvement over the statement of principles previously published in June 1936. Nevertheless, it still contains spots where further burnishing would appear to contribute both to desirable refinement and to greater harmony between the principles and the fundamental thesis upon which they are based. In the preparatory note the Committee states that "In the corporate field the most important use of accounting lies in the preparation of statements of financial position and of operating results." In the basic assumption the Committee also refers to the accounting statements as financial statements. The term financial position is equivocal. While it implies that it is the general monetary position of a firm that is being presented, or that a firm's status is being exhibited in monetary terms, the financial position presented in the balance sheet is a specific variety of financial position.